Transactions that mediate the contribution to a business association - Ханієва, Фатіма Магомедівна (Theory and practice of jurisprudence, 2019)
The article analyzes the transactions that mediate the contribution to the business association. Attention is paid to determining the legal nature of the transactions made by the founders/participants when they are making the contributions to the statutory (folding) capital. The author also conducted a comparative legal analysis of the Ukraine’s legislation with the legislation of foreign countries (France, Czech Republic, Latvia, Poland, etc.). It is concluded that in the initial creation of a business company the sole founder of the contribution is a unilateral substantive transaction, which is performed in order to execute the decision on the establishment of the company. However, if the partnership is founded by two or more founders, the actions of the founders in making contributions are a unilateral action that accompanies or commits a binding contract of the founders. Similarly, making additional deposits when a third party enters the Private Limited Сompany/Additional Liability Company should be considered as a bilateral real estate transaction, which is performed for the implementation of the contract on additional contribution, and the contribution by the members of the company – a bilateral real estate transaction, which is performed for the execution of the decision of the general meeting to attract additional fees. deposits or an additional contribution agreement. In this case, the deposit transaction as a real transaction (transfer of deposit) cannot be automatically invalidated if the binding agreement of the founders is invalidated